ANALISIS KEPUASAN PENYELENGGARAANPENERBITAN E-KTP DI TEMPAT PEREKAMAN DATA KEPENDUDUKAN (TPDK) DISDUKCAPIL KECAMATAN SEMARANG BARAT - Elisabeth Kezia Devantie; Herbasuki Nurcahyanto (Journal of Public Policy and Management Review, 2018)
Enhancing the quality of public services is needed to fulfill the satisfaction of society to the service as expected. Satisfaction is the level of one’s feelings after comparing perceived performance with expectations. This research aims to determine the level of satisfaction of community members related to e-ID card service users in the process of organizing e-ID card publishing and dimensions that need to be improved to increase satisfaction on the quality service at TPDK in Disdukcapil West Semarang Sub District. The author uses quantitative research type by the number of samples as many as 97 respondents as services users at TPDK in Disdukcapil West Semarang Sub District. This research uses the measurement of satisfaction through the 6 dimensions i.e. tangible services, reliability, responsiveness, assurance, empathy, and communication by comparing performance (X) and expectations (Y) that raise the feeling of satisfaction or disatisfaction. The results showed there were three dimensions with three determinants of service quality which are considered important in determining the satisfaction level of society. Which has high expectations, but the level of performance is low so that, it can be said to be less satisfactory and unsatisfactory. The three dimensions: Responsiveness, which includes a factor of quick service, Assurance, including the factor of friendliness and courtesy, Communication officers, including the factor of easement in getting information. The quality of six dimensions with 19 factors has an average of performance level 2.74 and the level of hope 3.48 with the rate of conformity of 78.69 which is categorized satisfacfactory